(untitled) (Global Scientific Review, 2025)
During operation and storage, agricultural machines are exposed to the atmosphere, soil, toxic substances, organic and mineral fertilizers. During operation, soil processing machines interact with the soil not only by abrasive wear (bending), but also by corrosion. In this article, corrosion classifications are studied on a scientific basis.